Analisis Sistem Pencatatan Akuntansi Zakat terhadap Pelaporan Dana Zakat pada BAZNAS Kabupaten Garut - Sri Lestari Anggraeni; Firman Yudhanegara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the zakat accounting recording system and its implications for zakat fund reporting at BAZNAS Garut Regency with reference to PSAK 409. The research method employed is descriptive qualitative, conducted through interviews with BAZNAS officials and analysis of ZIS data collection for the 2023–2024 period. The findings reveal that the current recording process remains manual and semi-digital, which creates challenges in terms of accuracy and consistency of reporting. Nevertheless, the data indicate a 46.64% increase in ZIS collection, particularly in zakat maal and unrestricted donations. These results highlight the need for strengthening human resource (HR) capacity, developing an information technology–based recording system, and implementing regular internal audits to enhance accountability and transparency of zakat reports. Therefore, this study provides strategic recommendations for BAZNAS Garut Regency to optimize zakat fund management in order to ensure sustainability, strengthen public trust, and improve the overall quality of organizational governance.